Sex- and age-specific reference intervals for diagnostic ratios reflecting relative activity of steroidogenic enzymes and pathways in adults. - Valentin Rousson (Public Library of Science (PLoS), 2021)
Objective Diagnostic ratios calculated from urinary steroid hormone metabolites are used as a measure for the relative activity of steroidogenic enzymes or pathways in the clinical investigation of steroid metabolism disorders. However, population-based sex- and age-specific reference intervals and day-night differences in adults are lacking. Methods Sixty-five diagnostic ratios were calculated from steroid metabolites measured by GC-MS in day- and night-time and in 24-hour urine from 1128 adults recruited within the Swiss Kidney Project on Genes in Hypertension (SKIPOGH), a population-based, multicenter cohort study. Differences related to sex, age and day- and night-time were evaluated and reference curves in function of age and sex were modelled by multivariable linear mixed regression for diagnostic ratios and were compared to values from the literature. Results Most ratios had sex- and age-specific relationships. For each ratio, percentiles were plotted in function of age and sex in order to create reference curves and sex- and age-specific reference intervals derived from 2.5th and 97.5th percentiles were obtained. Most ratios reflected a higher enzyme activity during the day compared to the night. Conclusions Sex- and age-specific references for 24 hours, day and night urine steroid metabolite ratios may help distinguishing between health and disease when investigating human disorders affecting steroid synthesis and metabolism. The day-night differences observed for most of the diagnostic ratios suggest a circadian rhythm for enzymes involved in human steroid hormones metabolism.